Tandem perovskite solar cell and manufacturing method thereof
The laser edge isolation process addresses the inefficiencies in tandem perovskite solar cell manufacturing by severing shunt paths, improving performance and reducing output loss through a more efficient manufacturing process.
Patent Information
- Application Number
- KR1020250124561
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2025-04-02
- Filing Date
- 2025-09-03
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-09-03
AI Technical Summary
Conventional methods for manufacturing tandem perovskite solar cells face issues with mass production capabilities, long deposition times, and the creation of shunt paths due to the deposition of transparent electrodes without directionality, leading to charge recombination and heat generation.
A laser edge isolation process is introduced after depositing the transparent electrode, severing shunt paths by cutting the electrode ends perpendicular to the surface, allowing charge to move towards the charge selective layer.
This method enhances the performance of perovskite solar cells by breaking shunt paths and reducing output loss, resulting in a simpler and more efficient manufacturing process.
Smart Images

Figure 112025101076769-PAT00015_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a tandem perovskite solar cell in which a laser edge isolation process is introduced in a process for manufacturing a solar cell, and a method for manufacturing the same. Background Technology
[0003] To address the depletion of fossil fuels and the global environmental problems caused by their use, research on renewable and clean alternative energy sources such as solar, wind, and hydroelectric power is actively underway. Among these, interest in solar cells, which directly convert sunlight into electrical energy, is increasing significantly. Here, a solar cell refers to a battery that generates current and voltage by utilizing the photovoltaic effect, which absorbs light energy from sunlight to generate electrons and holes.
[0004] Currently, it is possible to manufacture np diode-type silicon (Si) single-crystal-based solar cells with a light energy conversion efficiency of over 20%, and they are being used in actual solar power generation. There are also solar cells using compound semiconductors such as gallium arsenide (GaAs), which have even better conversion efficiency. However, these inorganic semiconductor-based solar cells require materials purified to a very high degree of purity to achieve high efficiency, so a large amount of energy is consumed in purifying the raw materials. Furthermore, expensive process equipment is required to process the raw materials into single crystals or thin films, which limits the ability to lower the manufacturing cost of solar cells and has been a stumbling block to large-scale operation.
[0005] Accordingly, in order to manufacture solar cells at a low cost, it is necessary to significantly reduce the cost of materials or manufacturing processes used as core components; as an alternative to inorganic semiconductor-based solar cells, research is being conducted on perovskite solar cells, which can be manufactured using low-cost materials and processes.
[0006] The general structural formula of a perovskite structure is ABX3, in which an anion is located at the X site, a large cation is located at the A site, and a small cation is located at the B site.
[0007] Unlike crystalline materials, perovskite compounds, which are polyionic solids, contain ionic defects. When devices composed of perovskites are exposed to external environments (heat, light, bias, stress, moisture, etc.), these defects act as factors that impair device performance. This causes problems that complicate not only the stability of perovskite solar cells but also the definition of steady-state conditions and the accurate measurement of performance parameters.
[0008] Meanwhile, a tandem perovskite solar cell can be manufactured by stacking a perovskite solar cell capable of absorbing light in the short wavelength region on top of a crystalline silicon solar cell. Specifically, as shown in FIG. 1, in manufacturing a tandem solar cell comprising a stack in which a bottom cell (1), a recombination layer (10), a hole transport layer (20), a perovskite light absorption layer (30), an intermediate layer (40), an electron transport layer (50), and a transparent electrode (60) are sequentially stacked, a bottom-up method is mainly used, but this method has the disadvantages of lacking mass production capability and long deposition times and un-deposited areas due to the use of trays. To solve these problems, a top-down method must be introduced to achieve high speed and full-surface deposition. However, when depositing a transparent electrode (60) in a top-down manner on top of an electron transport layer (50), it is difficult to deposit it only on the upper surface of the electron transport layer (50), so it is deposited on the side of the tandem perovskite solar cell without directionality, and thus a shunt path is created, and as a result, it cannot perform the role of charge selectivity, so charge recombination is accelerated and ultimately heat is generated in the tandem perovskite solar cell. Prior art literature
[0010] Korean Registered Patent No. 10-2019310 (Publication Date: March 30, 2015) The problem to be solved
[0011] The present invention was devised to overcome the aforementioned problems, and aims to provide a tandem perovskite solar cell and a method for manufacturing the same, which can produce a perovskite solar cell with excellent performance by introducing a laser edge isolation process after depositing a transparent electrode in the perovskite solar cell manufacturing process, thereby severing the shunt path and allowing charge to move toward the charge selective layer. means of solving the problem
[0013] To solve the above-mentioned problem, the method for manufacturing a perovskite solar cell of the present invention may include a first step of preparing a laminate in which a hole transport layer, a perovskite light absorption layer, and an electron transport layer are sequentially stacked; a second step of forming a transparent electrode on top of the electron transport layer; a third step of cutting both ends of the upper part of the transparent electrode in a direction perpendicular to one surface of the transparent electrode through a laser edge isolation process; and a fourth step of forming a metal electrode on top of the transparent electrode.
[0014] As a preferred embodiment of the present invention, the laminate may further include an intermediate layer between the perovskite light absorption layer and the electron transport layer.
[0015] As a preferred embodiment of the present invention, the laser edge isolation process can be performed using a pulsed laser under conditions of a laser wavelength of 300 to 400 nm and a pulse duration of 5 to 15 Ps.
[0016] As a preferred embodiment of the present invention, the laser edge isolation process can be performed under conditions of power 0.1 to 1.0 W, scan speed 500 to 1,500 mm / s, repetition rate 300 to 700 kHz, scanner z-axis 5.0 to 15.0 mm, and spot distance 0.5 to 5 μm.
[0017] As a preferred embodiment of the present invention, the transparent electrode may be a transparent thin film having ITO (Indium Tin Oxide), FTO (Fluorine-doped Tin Oxide), ATO (Sb2O3-doped Tin Oxide), GTO (Gallium-doped Tin Oxide), ZTO (tin-doped zinc oxide), ZTO:Ga (gallium-doped ZTO), IGZO (Indium-gallium-zinc oxide), IZO (Indium-doped zinc oxide), or AZO (Aluminum-doped zinc oxide) deposited thereon.
[0018] As a preferred embodiment of the present invention, the perovskite light-absorbing layer may include a perovskite material represented by the following chemical formula 1.
[0019] [Chemical Formula 1]
[0020] CMX3
[0021] In the above chemical formula 1, C is a monovalent cation, M is a divalent cation, and X is a monovalent anion.
[0022] Meanwhile, the method for manufacturing a tandem perovskite solar cell of the present invention may include a first step of preparing a laminate in which a bottom cell, a recombination layer, a hole transport layer, a perovskite light absorption layer, and an electron transport layer are sequentially stacked; a second step of forming a transparent electrode on top of the electron transport layer; a third step of cutting both ends of the upper portion of the transparent electrode in a direction perpendicular to one surface of the transparent electrode through a laser edge isolation process; and a fourth step of forming a metal electrode on top of the transparent electrode.
[0023] As a preferred embodiment of the present invention, through a third step laser edge isolation process, the recombination layer, hole transport layer, perovskite light absorption layer, and electron transport layer may be cut, while the bottom cell may not be cut.
[0024] As a preferred embodiment of the present invention, the bottom cell of the first step may be a polycrystalline silicon solar cell, a crystalline silicon solar cell, a perovskite solar cell, a gallium arsenide (GaAs) solar cell, a cadmium telluride (CdTe) solar cell, a CIGS (CuInGaSe) solar cell, a CZTS (Cu2ZnSnS4) solar cell, an organic solar cell, a dye-sensitized solar cell, or a group 3-5 compound solar cell.
[0025] Furthermore, the tandem perovskite solar cell of the present invention comprises a bottom cell, a recombination layer, and a top cell stacked sequentially, wherein the top cell may include a stacked body in which a hole transport layer, a perovskite light absorption layer, an electron transport layer, and a transparent electrode are stacked sequentially.
[0026] As a preferred embodiment of the present invention, the tandem perovskite solar cell of the present invention is cut in a vertical direction on one surface of the transparent electrode, so that the recombination layer and the upper cell can be divided into three.
[0027] As a preferred embodiment of the present invention, the tandem perovskite solar cell of the present invention is cut in a vertical direction on one surface of the transparent electrode, so that part or all of the upper cell can be divided into three.
[0028] As a preferred embodiment of the present invention, the tandem perovskite solar cell of the present invention may have a recombination layer and / or an upper cell formed with a central part and both ends based on a cross-sectional plane.
[0029] As a preferred embodiment of the present invention, the tandem perovskite solar cell of the present invention may have a cross-sectional width of 1 to 40 μm.
[0030] As a preferred embodiment of the present invention, the tandem perovskite solar cell of the present invention can satisfy the following condition (1).
[0031] (1) 99.45% ≤ ≤ 99.95%
[0032] In the above condition (1), A represents the length of the central part, B represents the length of one end part, and C represents the width of the cross-section.
[0033] As a preferred embodiment of the present invention, the stack of the tandem perovskite solar cell of the present invention may further include a metal electrode formed on one surface of the central portion of the transparent electrode.
[0034] As a preferred embodiment of the present invention, the stack of the tandem perovskite solar cell of the present invention may further include an intermediate layer between the perovskite light absorption layer and the electron transport layer. Effects of the invention
[0036] The tandem perovskite solar cell of the present invention and the method for manufacturing the same can manufacture a perovskite solar cell with excellent performance by breaking the shunt path so that charge can move toward the charge selective layer.
[0037] In addition, the tandem perovskite solar cell and the method for manufacturing the same according to the present invention have a simple and easy manufacturing process.
[0038] In addition, the tandem perovskite solar cell of the present invention and the method for manufacturing the same can reduce output loss by reducing the loss area. Brief explanation of the drawing
[0040] Figure 1 is a conceptual diagram illustrating a shunt path that occurs when a transparent electrode is deposited on top of an electron transport layer in a conventional method for manufacturing a tandem perovskite solar cell. FIG. 2 is a conceptual diagram illustrating a method for manufacturing a tandem perovskite solar cell according to a preferred embodiment of the present invention, wherein a laser edge isolation process is performed after depositing a transparent electrode on top of an electron transport layer. FIGS. 3 and 4 are cross-sectional views of a tandem perovskite solar cell according to a preferred embodiment of the present invention. FIGS. 5 and 6 are cross-sectional views of a tandem perovskite solar cell according to another preferred embodiment of the present invention. Specific details for implementing the invention
[0041] The present invention will be described in more detail below.
[0042] Conventional manufacturing of perovskite solar cells primarily utilizes a bottom-up method, but this method suffers from poor mass production capabilities and has disadvantages such as un-deposited areas and long deposition times due to the use of trays. To address these issues, a top-down method must be introduced to achieve high-speed and full-surface deposition. However, when depositing a transparent electrode on top of an electron transport layer using the top-down method, it is difficult to deposit it only on the upper surface of the electron transport layer. Consequently, the electrode is deposited on the sides of the perovskite solar cell without directionality, creating shunt paths. This prevents the electrode from functioning as a charge selector, which accelerates charge recombination and ultimately leads to heat generation in the perovskite solar cell.
[0043] Accordingly, the present invention aims to provide a tandem perovskite solar cell with excellent performance and a method for manufacturing the same by introducing a laser edge isolation process after depositing a transparent electrode in the perovskite solar cell manufacturing process, thereby severing the shunt path and allowing charges to move toward the charge selective layer.
[0045] The method for manufacturing a perovskite solar cell according to the present invention comprises steps 1 through 4.
[0046] First, the first step of the method for manufacturing a perovskite solar cell according to the present invention may be to prepare a laminate in which a hole transport layer, a perovskite light absorption layer, and an electron transport layer are sequentially stacked. At this time, the laminate may further include an intermediate layer between the perovskite light absorption layer and the electron transport layer.
[0047] A hole transport layer (HTL, or hole transport layer) is a layer that transports holes formed in a perovskite light-absorbing layer while simultaneously blocking the movement of electrons, and may include inorganic and / or organic hole transport materials.
[0048] At this time, the inorganic hole transport material may include one or more selected from nickel oxide (NiOx), CuSCN, CuCrO2, CuI, MoO, and V2O5.
[0049] In addition, organic hole transporters include carbazole derivatives, polyarylalkane derivatives, phenylenediamine derivatives, arylamines, amino-substituted chalcone derivatives, styrylanthracene derivatives, fluorene derivatives, hydrazone derivatives, stilbene derivatives, silazane derivatives, aromatic tertiary amine compounds, styrylamine compounds, aromatic dimethylidine compounds, porphyrin compounds, phthalocyanine compounds, polythiophene derivatives, polypyrrole derivatives, polyparaphenylenevinylene derivatives, pentacene, coumarin 6 (3-(2-benzothiazolyl)-7-(diethylamino)coumarin), ZnPC (zinc phthalocyanine), CuPC (copper phthalocyanine), TiOPC (titanium oxide phthalocyanine), Spiro-MeOTAD(2,2',7,7'-tetrakis(N,Np-dimethoxyphenylamino)-9,9'-spirobifluorene), F16CuPC(copper(II) 1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H,31H-phthalocyanine), SubPc (boron subphthalocyanine chloride) and N3(cis-di(thiocyanato)-bis(2,2'-bipyridyl-4,4'-dicarboxylic acid)-ruthenium(II), P3HT(poly[3-hexylthiophene]), MDMO-PPV(poly[2-methoxy-5-(3',7'-dimethyloctyloxyl)]-1,4-phenylene vinylene), MEH-PPV(poly[2-methoxy-5-(2''-ethylhexyloxy)-p-phenylene vinylene]), P3OT(poly(3-octyl thiophene)), POT(poly(octyl thiophene)), P3DT(poly(3-decyl thiophene)),P3DDT(poly(3-dodecyl thiophene), PPV(poly(p-phenylene vinylene)), TFB(poly(9,9'-dioctylfluorene-co-N-(4-butylphenyl)diphenyl amine), 폴리아닐린(Polyaniline), Spiro-MeOTAD([2,22′,7,77′-tetrkis (N,N-di-pmethoxyphenyl amine)-9,9,9′-spirobi fluorine]), PCPDTBT(Poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl-4H-cyclopenta [2,1-b:3,4-b']dithiophene-2,6-diyl]], Si-PCPDTBT(poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl]), PBDTTPD(poly((4,8-diethylhexyloxyl), PFDTBT(poly[2,7-(9-(2-ethylhexyl)-9-hexyl-fluorene)-alt-5,5-(4', 7, -di-2-thienyl-2',1', 3'-benzothiadiazole)]), PFO-DBT(poly[2,7-.9,9-(dioctyl-fluorene)-alt-5,5-(4',7'-di-2-.thienyl-2', 1', 3'-benzothiadiazole)]), PSiFDTBT(poly[(2,7-dioctylsilafluorene)-2,7-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadiazole)-5,5′-diyl]), PCDTBT(Poly [[9-(1-octylnonyl)-9H-carbazole-2,7-diyl] -2,5-thiophenediyl-2,1,3-benzothiadiazole-4,7-diyl-2,5-thiophenediyl]), PFB(poly(9,It may include one or more selected from 9′-dioctylfluorene-co-bis(N,N′-(4,butylphenyl))bis(N,N′-phenyl-1,4-phenylene)diamine), F8BT(poly(9,9′-dioctylfluorene-cobenzothiadiazole), PEDOT (poly(3,4-ethylenedioxythiophene)), PEDOT:PSS poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate), PTAA (poly(triarylamine)), 2-PACz, MeO-2PACz, Br-2PACz, Me-4PACz, MeO-4PACz, and 6-PACz.
[0050] In addition, methods for forming a hole transport layer include coating methods and vacuum deposition methods, and coating methods include gravure coating, bar coating, printing, spraying, spin coating, dip coating, and die coating.
[0051] In addition, there is no separate limit on the thickness of the hole transport layer, but preferably it can have a thickness of 5 nm to 40 nm, and more preferably 10 nm to 30 nm.
[0052] The perovskite light-absorbing layer may include a perovskite material represented by the following chemical formula 1.
[0053] [Chemical Formula 1]
[0054] CMX3
[0055] In the above Formula 1, C is a monovalent cation and may include an amine, ammonium, a Group 1 metal, a Group 2 metal, and / or other cation or cation-like compound, preferably formamidinium (FA), methylammonium (MA), FAMA, CsFAMA, CsFA, or N(R)4 +(Here, R may be the same or different group, and R may be a straight-chain alkyl group having 1 to 5 carbon atoms, a branched-chain alkyl group having 3 to 5 carbon atoms, a phenyl group, an alkylphenyl group, an alkoxyphenyl group, or an alkyl halide.)
[0056] In addition, M of Chemical Formula 1 is a divalent cation and may include one or two types selected from Fe, Co, Ni, Cu, Sn, Pb, Bi, Ge, Ti, Eu, and Zr.
[0057] In addition, X of Formula 1 is a monovalent anion and may include one or more halide elements selected from F, Cl, Br, and I and / or a Group 16 anion, and in a preferred example, X is I x Br 3-x (0 ≤ x ≤ 3) can be.
[0058] And, as a preferred embodiment of Chemical Formula 1, FAPbI x Br 3-x (0 ≤ x ≤ 3), MAPbI x Br 3-x (0 ≤ x ≤ 3), CSFAPbI x Br 3-x (0 ≤ x ≤ 3), CSMAFAPbI x Br 3-x (0 ≤ x ≤ 3), CH3NH3PbX3(X= Cl, Br, I, BrI2, or Br2I), CH3NH3SnX3(X= Cl, Br or I), CH(=NH)NH3PbX3(X= Cl, Br, I, BrI2, or Br2I) or CH(=NH)NH3SnX3(X= Cl, Br or I).
[0059] Meanwhile, the perovskite light-absorbing layer may be a single layer composed of the same perovskite material, or a multilayer structure in which multiple layers composed of different perovskite materials are stacked, and may include a different type of perovskite material different from the one type of perovskite material having a pillar shape, plate shape, needle shape, wire shape, rod shape, etc. within the light-absorbing layer composed of one type of perovskite material.
[0060] In addition, methods for forming a perovskite light-absorbing layer may include deposition processes and solution processes. The deposition process may be any general deposition process used in the industry, such as thermal evaporation, vacuum deposition, atomic layer deposition (ALD), chemical vapor deposition (CVD), or physical vapor deposition (PVD). The solution process may be any general solution process used in the industry, such as spin coating, slot die coating, blade coating, printing coating, gravure coating, or spray coating.
[0061] In addition, there is no separate limit on the thickness of the perovskite light absorption layer, but preferably it can have a thickness of 50 nm to 800 nm, and more preferably 300 nm to 600 nm.
[0062] The intermediate layer may contain lithium fluoride (LiF).
[0063] In addition, deposition processes and solution processes can be performed as methods for forming an intermediate layer. The deposition process can be any general deposition process used in the industry, such as thermal evaporation, vacuum deposition, atomic layer deposition (ALD), chemical vapor deposition (CVD), and physical vapor deposition (PVD). The solution process can be any general solution process used in the industry, such as spin coating, slot die coating, blade coating, printing coating, gravure coating, and spray coating.
[0064] In addition, there is no separate limit on the thickness of the intermediate layer, but preferably it can have an average thickness of 0.5 to 3 nm, and more preferably 0.5 to 1 nm.
[0065] The electron transporting layer (ETL) is a layer that transports electrons formed in the perovskite light-absorbing layer while simultaneously blocking the movement of holes.
[0066] The electron transport layer may include one or more materials selected from fullerene-based organic materials and inorganic materials. In this case, the fullerene-based organic materials may include one or more materials selected from C60 fullerene, C70 fullerene, PC60BM and PC70BM, and ICBA, and the inorganic materials may include one or more materials selected from tin oxide (SnOx), tin oxide (SnO2), titanium dioxide (TiO2), zinc oxide (ZnO), cerium oxide (CeO2), barium tin oxide (BaSnO3), niobium hydroxide (NbOH), and niobium pentoxide (Nb2O5).
[0067] Additionally, the electron transport layer may further include organic materials, and the organic materials may be non-fullerene derivatives, naphthalene derivatives, conjugate polymer derivatives, NDI-based polyer, ITIC (2,2'-((2Z,2'Z)-((4,4,9,9-tetrakis(4-hexylphenyl)-4,9-dihydro-s-indaceno[1,2-b:5,6-b']dithiophene-2,7-diyl)bis(methanylylidene))bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))dimalononitrile, PEI (Poly(ethyleneimine)), PEIE (Poly(ethylenimine)-ethoxylated), P3HT (Poly(3-hexylthiophene), TTF (Tetrathiafulvalene), BCP (Bathocuproine) It may include one or more selected from among.
[0068] In addition, deposition processes and solution processes can be performed as methods for forming the electron transport layer. The deposition process can be any general deposition process used in the industry, such as thermal evaporation, vacuum deposition, atomic layer deposition (ALD), chemical vapor deposition (CVD), and physical vapor deposition (PVD). The solution process can be any general solution process used in the industry, such as spin coating, slot die coating, blade coating, printing coating, gravure coating, and spray coating.
[0069] In addition, there is no separate limit on the thickness of the electron transport layer, but preferably it can have an average thickness of 3 to 30 nm, and more preferably 5 to 20 nm.
[0071] The second step of the method for manufacturing a perovskite solar cell of the present invention may form a transparent electrode on top of the electron transport layer.
[0072] A transparent electrode can be formed through a deposition process. At this time, the deposition can be performed using a general deposition process used in the industry, and preferably, the deposition process can be performed using a sputtering method.
[0073] In addition, the transparent electrode may be a transparent thin film with ITO (Indium Tin Oxide), FTO (Fluorine-doped Tin Oxide), ATO (Sb2O3-doped Tin Oxide), GTO (Gallium-doped Tin Oxide), ZTO (tin-doped zinc oxide), ZTO:Ga (gallium-doped ZTO), IGZO (Indium-gallium-zinc oxide), IZO (Indium-doped zinc oxide), or AZO (Aluminum-doped zinc oxide) deposited thereon.
[0074] In addition, there is no separate limit on the thickness of the transparent electrode, but preferably it can have a thickness of 50 to 200 nm, and more preferably 50 to 80 nm.
[0076] Referring to FIG. 2, the third step of the method for manufacturing a perovskite solar cell of the present invention can cut both ends of the upper portion of the transparent electrode (60) in a vertical direction on one surface of the transparent electrode (60) through a laser edge isolation process.
[0077] Laser edge isolation is a process of etching the edge portion of a film, thin film, or layer using a laser. Although there are no specific limitations, as an example, it can be performed using a pulsed laser.
[0078] Specifically, the laser edge isolation process can be performed under picosecond conditions using a pulsed laser.
[0079] In addition, the laser edge isolation process can be performed using a pulsed laser under conditions of a laser wavelength of 300 to 400 nm, preferably 320 to 380 nm, and more preferably 350 to 370 nm. If the laser wavelength is 532 nm, the laser beam energy density decreases, and since the energy penetrates deep into the surface of the material and is converted into heat, the heat effect region widens, which may result in a problem of reduced precision compared to an energy wavelength of 355 nm. In this case, the line width to be processed cannot be satisfied, and area loss may occur as a result. In the case of an IR laser with a laser wavelength of 1064 nm, the energy penetrates deep into the material, widening the heat effect region, and since the thermal energy is high, a shock wave phenomenon exists, which may cause problems with precision processing.
[0080] In addition, the laser edge isolation process can be performed using a pulsed laser with a pulse duration of 5 to 15 Ps, preferably 7 to 13 Ps, and more preferably 9 to 11 Ps. If the pulse duration is less than 5 Ps, there may be economic issues, and if it exceeds 15 Ps, there may be precision processing issues.
[0081] In addition, the laser edge isolation process can be performed using a pulsed laser under conditions of power 0.1 to 1.0 W, preferably 0.2 to 0.8 W, and more preferably 0.3 to 0.6 W.
[0082] In addition, the laser edge isolation process can be performed using a pulsed laser under conditions of a scan speed of 500 to 1,500 mm / s, preferably 800 to 1,200 mm / s, and more preferably 900 to 1,100 mm / s. If the scan speed is less than 500 mm / s, there may be a problem where the laser depth becomes excessively deep and the processing line width becomes wide. If the scan speed exceeds 1,500 mm / s, the spot distance may become wide, causing the laser line to become a dotted line rather than a solid line, which may result in a problem where the desired insulation is not achieved.
[0083] In addition, the laser edge isolation process can be performed using a pulsed laser under conditions of a repetition rate of 300 to 700 kHz, preferably 400 to 600 kHz, and more preferably 450 to 550 kHz. If the repetition rate is less than 300 kHz, the spot distance widens, and the laser line may become a dotted line rather than a solid line, which may result in a problem where the desired insulation is not achieved. If the repetition rate exceeds 700 kHz, there may also be a problem where the desired insulation is not achieved.
[0084] In addition, the laser edge isolation process can be performed using a pulsed laser under conditions where the scanner z-axis is 5.0 to 15.0 mm, preferably 7.0 to 13.0 mm, and more preferably 10.0 to 12.0 mm. If the scanner z-axis is less than 5.0 mm, not only is precision machining difficult, but there may also be a problem of damaging the perovskite solar cell being manufactured, and if it exceeds 15.0 mm, there may be a problem of inefficient machining.
[0085] In addition, the laser edge isolation process can be performed using a pulsed laser under conditions of a spot distance of 0.5 to 5 μm, preferably 1.0 to 3 μm, and more preferably 1.5 to 2.5 μm. If the spot distance is less than 0.5 μm, there may be a problem where the laser insulation depth increases and the processing line width increases unnecessarily, and if it exceeds 5 μm, there may be a problem where leakage occurs due to insufficient insulation.
[0087] The fourth step of the method for manufacturing a perovskite solar cell of the present invention may form a metal electrode on top of a transparent electrode that has undergone a laser edge isolation process.
[0088] A metal electrode can be formed by patterning a metal material on top of a transparent electrode. Specifically, the patterning process is largely composed of deposition, lithography, and etching. A metal electrode can be formed on top of a transparent electrode by laying a metal material in the form of a thin film on one side of a substrate, printing a pattern by exposure, and then removing the unnecessary parts. Additionally, the patterning process can be performed using a screen printing method with a metal paste containing a metal material. More specifically, the metal electrode may be composed of a plurality of bus bar electrodes arranged in a horizontal direction and a plurality of finger electrodes arranged in a vertical direction relative to the bus bar electrodes.
[0089] In addition, the metal material may include one or more selected from Pt, Au, Ni, Cu, Ag, In, Ru, Pd, Rh, Ir, Os, C, and conductive polymers.
[0090] In addition, there is no separate limit on the thickness of the metal electrode, but preferably, it can have a thickness of 50 nm to 15 µm.
[0092] Meanwhile, the method for manufacturing a tandem perovskite solar cell of the present invention includes steps 1 to 4.
[0093] The first step of the method for manufacturing a tandem perovskite solar cell of the present invention may be to prepare a laminate in which a bottom cell, a recombination layer, a hole transport layer, a perovskite light absorption layer, and an electron transport layer are sequentially stacked. At this time, an intermediate layer may be further included between the perovskite light absorption layer and the electron transport layer, and the hole transport layer, the perovskite light absorption layer, the intermediate layer, and the electron transport layer are each as described above.
[0094] The bottom cell may be a polycrystalline silicon solar cell, a crystalline silicon solar cell, a perovskite solar cell, a gallium arsenide (GaAs) solar cell, a cadmium telluride (CdTe) solar cell, a CIGS (CuInGaSe) solar cell, a CZTS (Cu2ZnSnS4) solar cell, an organic solar cell, a dye-sensitized solar cell, or a group 3-5 compound solar cell.
[0095] In addition, there is no separate limit on the thickness of the lower cell, but it can preferably have a thickness of 140 to 250 μm, and more preferably 160 to 200 μm.
[0096] In addition, when using an n- or p-type impurity-doped silicon solar cell as a bottom cell, the n- or p-type impurity-doped silicon solar cell can be used after removing the SiOx oxide film by treating it with hydrofluoric acid and then removing the residual hydrofluoric acid using ultrapure water.
[0097] The recombination layer is a layer that induces the recombination of electrons and holes generated in the bottom cell and the perovskite light absorption layer, and may be a transparent thin film with ITO (Indium Tin Oxide), FTO (Fluorine-doped Tin Oxide), ATO (Sb2O3-doped Tin Oxide), GTO (Gallium-doped Tin Oxide), ZTO (tin-doped zinc oxide), ZTO:Ga (gallium-doped ZTO), IGZO (Indium-gallium-zinc oxide), IZO (Indium-doped zinc oxide), or AZO (Aluminum-doped zinc oxide) deposited thereon.
[0098] In addition, as an example of forming a recombination layer, a recombination layer can be formed on the upper part of the lower cell through a sputtering process.
[0099] In addition, there is no separate limitation on the thickness of the recombination layer, but it can preferably have a thickness of 5 nm to 50 nm, and more preferably 10 nm to 25 nm.
[0101] The second step of the method for manufacturing a tandem perovskite solar cell of the present invention may involve forming a transparent electrode on top of the electron transport layer. At this time, the transparent electrode is as described above.
[0103] The third step of the method for manufacturing a tandem perovskite solar cell according to the present invention may involve cutting both ends of the upper portion of the transparent electrode in a direction perpendicular to one surface of the transparent electrode through a laser edge isolation process. At this time, the laser edge isolation process is as described above. Additionally, through the laser edge isolation process, the recombination layer, the hole transport layer, the perovskite light absorption layer, and the electron transport layer may be cut, while the bottom cell may not be cut. Additionally, through the laser edge isolation process, the hole transport layer, the perovskite light absorption layer, and the electron transport layer may be cut, while the recombination layer and the bottom cell may not be cut.
[0104] In addition, through a laser edge isolation process, a portion of the hole transport layer, the perovskite light absorption layer, and the electron transport layer may be cut, while another portion of the hole transport layer, the recombination layer, and the bottom cell may not be cut.
[0106] The fourth step of the method for manufacturing a tandem perovskite solar cell of the present invention may form a metal electrode on top of a transparent electrode. At this time, the metal electrode is as described above.
[0108] Furthermore, the perovskite solar cell of the present invention may be manufactured by the method for manufacturing the perovskite solar cell of the present invention described above.
[0110] Meanwhile, the tandem perovskite solar cell of the present invention may be manufactured by the method for manufacturing the tandem perovskite solar cell of the present invention described above.
[0112] Furthermore, referring to FIGS. 3 and 4, the tandem perovskite solar cell of the present invention has a structure in which a lower cell (1), a recombination layer (10), and an upper cell (2) are sequentially stacked, and the upper cell (2) may include a stack in which a hole transport layer (20), a perovskite light absorption layer (30), an electron transport layer (50), and a transparent electrode (60) are sequentially stacked. At this time, an intermediate layer (40) may be further included between the perovskite light absorption layer (30) and the electron transport layer (50), and the lower cell (1), the recombination layer (10), the hole transport layer (20), the perovskite light absorption layer (30), the intermediate layer (40), the electron transport layer (50), and the transparent electrode (60) are each as described above.
[0113] Specifically, the tandem perovskite solar cell of the present invention can be cut in a vertical direction on one side of the transparent electrode (60) so that the recombination layer (10) and the upper cell (2) can be divided into three parts, and the recombination layer (10) and the upper cell (2) can be formed into a central part (3) and two end parts (4, 5) based on the cut surface (6, 7).
[0114] At this time, the cut surface (6, 7) may have a width of 1 to 40 μm, preferably 30 to 40 μm, and if the width of the cut surface exceeds 40 μm, there may be a problem with the performance of the solar cell being degraded.
[0115] The tandem perovskite solar cell of the present invention can satisfy the following condition (1).
[0116] (1) 99.45% ≤ ≤ 99.95%, preferably 99.65% ≤ ≤ 99.90%, more preferably 99.80% ≤ ≤ 99.85%
[0117] In the above condition (1), A represents the length of the central part (3), B represents the length of one end part (4 or 5), and C represents the width of the cross section (6 or 7).
[0118] If condition (1), If it is less than 99.45%, not only is the performance of the solar cell reduced, but there may also be a problem with the formation of a shunt path, and if it exceeds 99.95%, not only is the processability reduced, but there may also be a problem with reduced process reliability.
[0119] In addition, the tandem perovskite solar cell of the present invention may further include a metal electrode (70) formed on one surface of the central part (3) of the transparent electrode (60), and the metal electrode (70) is as described above.
[0121] Additionally, referring to FIG. 5, the tandem perovskite solar cell of the present invention is cut in a vertical direction on one side of the transparent electrode (60), so that the recombination layer (10) is not divided, and only the upper cell (2) can be divided into three parts, and the upper cell (2) can be formed into a central part (3) and two end parts (4, 5) based on the cut surface (6, 7).
[0122] Additionally, referring to FIG. 6, the tandem perovskite solar cell of the present invention is cut in a vertical direction on one side of the transparent electrode (60), so that a part of the recombination layer (10) and the upper cell (2) is not divided, and only another part of the upper cell (2) is divided into three parts, and the other part of the cut upper cell (2) can be formed into a central part (3) and two end parts (4, 5) based on the cut surface (6, 7).
[0123] At this time, the cut surface (6, 7) may have a width of 1 to 40 μm, preferably 30 to 40 μm, and may satisfy the following condition (1).
[0124] (1) 99.45% ≤ ≤ 99.95%, preferably 99.65% ≤ ≤ 99.90%, more preferably 99.80% ≤ ≤ 99.85%
[0125] In the above condition (1), A represents the length of the central part (3), B represents the length of one end part (4 or 5), and C represents the width of the cross section (6 or 7).
[0127] The present invention will be explained in more detail below through examples, but the following examples are not intended to limit the scope of the invention and should be interpreted as being for the purpose of aiding understanding of the invention.
[0129] Example 1: Preparation of a tandem silicon / perovskite heterojunction solar cell
[0130] (1) A silicon solar cell (thickness: 180 μm) doped with n or p-type impurities was prepared, and the SiOx oxide film was removed by treating it with hydrofluoric acid, and then the remaining hydrofluoric acid was removed using ultrapure water.
[0131] (2) A 10 nm thick recombination layer (ITO) was formed on the silicon solar cell from which the oxide film had been removed through a sputtering process.
[0132] (3) A 15 nm thick nickel oxide (NiOx) was deposited on the recombining layer by sputtering vacuum deposition, and a 3 nm thick Me-4PACz was coated on the deposited nickel oxide by spin coating to form a hole transport layer.
[0133] (4) A yellow light-absorbing layer solution formed by dissolving in dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) on top of a hole transport layer is formed by blade coating, and a perovskite light-absorbing layer (CSFAPbI) having a 600 nm thick perovskite crystal structure is formed by heat treatment at 150°C for 20 minutes. x Br 3-X (0 ≤ x ≤ 3)) was formed.
[0134] (5) A layer of lithium fluoride (LiF) with a thickness of 1 nm was deposited on the perovskite light-absorbing layer through an evaporator process to form an intermediate layer on the perovskite light-absorbing layer.
[0135] (6) C on top of the perovskite light-absorbing layer through a thermal evaporation (Evaporator) process 60 Fullerene (Fullerene C 60 After depositing ), tin oxide (SnO) is deposited through an ALD (atomic layer deposition) process. x An electron transport layer with an average thickness of 6 nm was formed by depositing ).
[0136] (7) A transparent electrode (ITO) with a thickness of 50 nm was formed on top of the electron transport layer through a sputtering process.
[0137] (8) Through the laser edge isolation process, both ends of the upper surface of the transparent electrode were cut in a direction perpendicular to one side of the transparent electrode. At this time, a pulsed laser was used for laser edge isolation, and the process was performed under picosecond, laser wavelength 355 nm, pulse duration 10 Ps, power 0.4 W, scan speed 1,000 mm / s, repetition rate 500 kHz, scanner z-axis 11.0 mm, and spot distance 2 µm. In addition, it was confirmed that the area loss through the laser edge isolation process was very small, at about 0.4% of the total area. In addition, the recombination layer, hole transport layer, perovskite light absorption layer, intermediate layer, electron transport layer, and transparent electrode were divided into three parts by cutting through a laser edge isolation process, and the recombination layer, hole transport layer, perovskite light absorption layer, intermediate layer, electron transport layer, and transparent electrode were formed into a central part and two end parts based on the cutting plane. In addition, the cutting plane had a width of 35 μm, and condition (1) It was confirmed that the calculated value was 99.83% (A represents the length of the central part, B represents the length of one end, and C represents the width of the cross-section).
[0138] (9) A silicon / perovskite heterojunction solar cell was manufactured by forming a metal electrode by depositing silver (Ag) to a thickness of 15 μm at a pressure of 65 N on the upper part of the central part of the transparent electrode through a screen printing process, thereby sequentially stacking a silicon solar cell, a recombination layer, a hole transport layer, a perovskite light absorption layer, an intermediate layer, an electron transport layer, a transparent electrode, and a metal electrode.
[0140] Comparative Example 1: Preparation of a tandem silicon / perovskite heterojunction solar cell
[0141] (1) A silicon solar cell (thickness: 180 μm) doped with n or p-type impurities was prepared, and the SiOx oxide film was removed by treating it with hydrofluoric acid, and then the remaining hydrofluoric acid was removed using ultrapure water.
[0142] (2) A 10 nm thick recombination layer (ITO) was formed on the silicon solar cell from which the oxide film had been removed through a sputtering process.
[0143] (3) A 15 nm thick nickel oxide (NiOx) was deposited on the recombining layer by sputtering vacuum deposition, and a 3 nm thick Me-4PACz was coated on the deposited nickel oxide by spin coating to form a hole transport layer.
[0144] (4) A yellow light-absorbing layer solution formed by dissolving in dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) on top of a hole transport layer is formed by blade coating, and a perovskite light-absorbing layer (CSFAPbI) having a 600 nm thick perovskite crystal structure is formed by heat treatment at 150°C for 20 minutes. x Br 3-X (0 ≤ x ≤ 3)) was formed.
[0145] (5) A layer of lithium fluoride (LiF) with a thickness of 1 nm was deposited on the perovskite light-absorbing layer through an evaporator process to form an intermediate layer on the perovskite light-absorbing layer.
[0146] (6) C on top of the perovskite light-absorbing layer through a thermal evaporation (Evaporator) process 60 Fullerene (Fullerene C 60 After depositing ), tin oxide (SnO) is deposited through an ALD (atomic layer deposition) process. x An electron transport layer with an average thickness of 6 nm was formed by depositing ).
[0147] (7) A transparent electrode (ITO) with a thickness of 50 nm was formed on top of the electron transport layer through a sputtering process.
[0148] (8) A silicon / perovskite heterojunction solar cell was manufactured by forming a metal electrode by depositing silver (Ag) to a thickness of 15 μm at a pressure of 65 N on top of a transparent electrode through a screen printing process, thereby sequentially stacking a silicon solar cell, a recombination layer, a hole transport layer, a perovskite light absorption layer, an intermediate layer, an electron transport layer, a transparent electrode, and a metal electrode.
[0150] Experimental Example 1: Measurement of Solar Cell Performance
[0151] For each of the tandem silicon / perovskite heterojunction solar cells prepared in Example 1 and Comparative Example 1, the efficiency was measured using a photovoltaic simulation device and a JV Keithley device, and the initial JV curve was used and is shown in Table 1 below.
[0153] Experimental Example 2: Measurement of Reverse Voltage of a Solar Cell
[0154] For each of the tandem silicon / perovskite heterojunction solar cells prepared in Example 1 and Comparative Example 1, after applying a leakage current evaluation, the reverse voltage was measured using a source meter in a dark state with a photovoltaic simulation device and is shown in Table 2 below.
[0156]
[0157]
[0159] As can be seen in Table 1, the tandem silicon / perovskite heterojunction solar cell prepared in Example 1 not only has superior power conversion efficiency compared to the tandem silicon / perovskite heterojunction solar cell prepared in Comparative Example 1, but also has superior maximum power point tracking (MPPT).
[0160] In addition, as can be seen in Table 2, the tandem silicon / perovskite heterojunction solar cell prepared in Comparative Example 1 measured 1.96 A in the -15 V reverse voltage measurement, and the tandem silicon / perovskite heterojunction solar cell prepared in Example 1 measured 0.71 A. Through this, it was confirmed that the -15 V reverse voltage decreased from 1.96 A to 0.71 A by performing the Laser Edge Isolation process.
[0162] Specific embodiments have been illustrated and described above. However, the invention is not limited to the aforementioned embodiments, and those skilled in the art may make various modifications without departing from the essence of the technical concept of the invention as described in the following claims.
Claims
Claim 1 A method for manufacturing a tandem perovskite solar cell comprising: a first step of preparing a laminate in which a bottom cell, a recombination layer, a hole transport layer, a perovskite light absorption layer, and an electron transport layer are sequentially stacked; a second step of forming a transparent electrode on top of the electron transport layer; a third step of cutting both ends of the top of the transparent electrode in a direction perpendicular to one surface of the transparent electrode through a laser edge isolation process; and a fourth step of forming a metal electrode on top of the transparent electrode; wherein, through the laser edge isolation process, the recombination layer, the hole transport layer, the perovskite light absorption layer, and the electron transport layer are cut, but the bottom cell is not cut. Claim 2 A method for manufacturing a tandem perovskite solar cell according to claim 1, wherein the laminate further comprises an intermediate layer between the perovskite light absorption layer and the electron transport layer. Claim 3 A method for manufacturing a tandem perovskite solar cell according to claim 1, wherein the laser edge isolation process is performed using a pulsed laser under conditions of a laser wavelength of 300 to 400 nm and a pulse duration of 5 to 15 Ps. Claim 4 A method for manufacturing a tandem perovskite solar cell according to claim 3, wherein the laser edge isolation process is performed under conditions of power 0.1 to 1.0 W, scan speed 500 to 1,500 mm / s, repetition rate 300 to 700 kHz, scanner z-axis 5.0 to 15.0 mm, and spot distance 0.5 to 5 μm. Claim 5 A method for manufacturing a tandem perovskite solar cell according to claim 1, wherein the transparent electrode is a transparent thin film deposited with ITO (Indium Tin Oxide), FTO (Fluorine-doped Tin Oxide), ATO (Sb2O3-doped Tin Oxide), GTO (Gallium-doped Tin Oxide), ZTO (tin-doped zinc oxide), ZTO:Ga (gallium-doped ZTO), IGZO (Indium-gallium zinc oxide), IZO (Indium-doped zinc oxide), or AZO (Aluminum-doped zinc oxide). Claim 6 A method for manufacturing a tandem perovskite solar cell according to claim 1, wherein the perovskite light-absorbing layer comprises a perovskite material represented by the following chemical formula 1. [Chemical Formula 1] CMX3 In the above chemical formula 1, C is a monovalent cation, M is a divalent cation, and X is a monovalent anion. Claim 7 A method for manufacturing a tandem perovskite solar cell comprising: a first step of preparing a laminate in which a bottom cell, a recombination layer, a hole transport layer, a perovskite light absorption layer, and an electron transport layer are sequentially stacked; a second step of forming a transparent electrode on top of the electron transport layer; a third step of cutting both ends of the top of the transparent electrode in a direction perpendicular to one surface of the transparent electrode through a laser edge isolation process; and a fourth step of forming a metal electrode on top of the transparent electrode; wherein, through the laser edge isolation process, the perovskite light absorption layer and the electron transport layer are cut, and the hole transport layer is cut in whole or in part, but the recombination layer and the bottom cell are not cut. Claim 8 A method for manufacturing a tandem perovskite solar cell according to claim 1, wherein the lower cell of the first step is a polycrystalline silicon solar cell, a crystalline silicon solar cell, a perovskite solar cell, a gallium arsenide (GaAs) solar cell, a cadmium telluride (CdTe) solar cell, a CIGS (CuInGaSe) solar cell, a CZTS (Cu2ZnSnS4) solar cell, an organic solar cell, a dye-sensitized solar cell, or a group 3-5 compound solar cell. Claim 9 A tandem perovskite solar cell in which a bottom cell, a recombination layer, and a top cell are sequentially stacked, wherein the top cell comprises a stack in which a hole transport layer, a perovskite light absorption layer, an electron transport layer, and a transparent electrode are sequentially stacked, and the recombination layer and the top cell are divided into three parts by cutting in a vertical direction of one surface of the transparent electrode, and the recombination layer and the top cell are formed into a central part and two end parts based on the cutting plane. Claim 10 A tandem perovskite solar cell according to claim 9, wherein each of the recombination layer and the upper cell has a cross-sectional area having a width of 1 to 40 μm and satisfies the following condition (1). (1) 99.45% ≤ ≤ 99.95% In the above condition (1), A represents the length of the central part, B represents the length of one end part, and C represents the width of the cross-section. Claim 11 In claim 9, the above laminate further comprises a metal electrode formed on one surface of the central portion of the transparent electrode, a tandem perovskite solar cell. Claim 12 In claim 9, the above laminate further comprises an intermediate layer between the perovskite light absorption layer and the electron transport layer, forming a tandem perovskite solar cell. Claim 13 A tandem perovskite solar cell in which a bottom cell, a recombination layer, and a top cell are sequentially stacked, wherein the top cell comprises a stack in which a hole transport layer, a perovskite light absorption layer, an electron transport layer, and a transparent electrode are sequentially stacked, and the hole transport layer, perovskite light absorption layer, electron transport layer, and transparent electrode of the top cell are cut in a vertical direction on one surface of the transparent electrode so as to divide them into three parts, and the hole transport layer, perovskite light absorption layer, electron transport layer, and transparent electrode of the top cell are formed into a central part and two end parts based on the cut surface. Claim 14 A tandem perovskite solar cell in which a bottom cell, a recombination layer, and a top cell are sequentially stacked, wherein the top cell comprises a stack in which a hole transport layer, a perovskite light absorption layer, an electron transport layer, and a transparent electrode are sequentially stacked, and the perovskite light absorption layer, the electron transport layer, and the transparent electrode of the top cell are divided into three parts by cutting in a vertical direction on one surface of the transparent electrode, and a portion of the hole transport layer of the top cell is cut in a vertical direction, and the perovskite light absorption layer, the electron transport layer, and the transparent electrode of the top cell are formed into a central part and two end parts based on the cut surface. Claim 15 A tandem perovskite solar cell according to claim 13 or 14, wherein the upper cell has a cross-sectional width of 1 to 40 μm and satisfies the following condition (1). (1) 99.45% ≤ ≤ 99.95% In the above condition (1), A represents the length of the central part, B represents the length of one end part, and C represents the width of the cross-section. Claim 16 A tandem perovskite solar cell according to claim 13 or 14, wherein the laminate further comprises a metal electrode formed on one surface of the central portion of the transparent electrode. Claim 17 A tandem perovskite solar cell according to claim 13 or 14, wherein the laminate further comprises an intermediate layer between the perovskite light absorption layer and the electron transport layer.
Citation Information
Patent Citations
Two-end perovskite heterojunction silicon laminated solar cell with high light conversion efficiency and preparation method thereof
CN112164729A
Solar cell and manufacturing method thereof
CN116940139A
Tandem solar cell and manufacturing method thereof
KR1020240040275A
